ANALISIS PENENTUAN TARIF RAWAT INAP BERDASARKAN VARIABLE COSTING PADA RUMAH SAKIT GMIM SILOAM SONDER - Pandey, Cristian M; Elim, Inggriani; Pinatik, Sherly (Universitas Sam Ratulangi, 2019)
The success of a hospital is very much determined by the accuracy of the leadership's ability to manage costs. The variable costing method is an alternative method for calculating the cost of production, which separates cost information according to behavior in relation to changes in the volume of activities.The purpose of this study was to analyze the determination of hospitalization rates based on variable costing at GMIM Siloam Sonder Hospital.The analytical method used in this study is a qualitative descriptive method. Where this method discusses a problem in detail by collecting data and processing it and concluding the results of the analysis. The results of the study according to calculations based on variable costing are the cost of a room per day per person hospitalized VIP rooms of Rp. 385,665 first class rooms of Rp. 246,391 class II rooms of Rp. 192.152 and class III rooms of Rp. 126,243 while the rates set by the hospital differ from those examined by the author through the coting variable method. So it needs to be evaluated because it is less relevant to the current conditions.